The practice of behavioural medicine - Pearce, S.; Wardle (Eds.), J. (Psicothema, 1990)
There is no shortage of books or research articles pointing to the effectiveness of psychological methods as applied to medical problems. And indeed the authors contributing to this edition present closely argued and well supported cases for such interventions and approaches. For anyone working within the specific diagnostic groups of hypertension, cardiac rehabilitation, injury to the CNS, pain, obesity, AIDS, diabetes, premenstrual syndrome and menopause, irritable bowel syndrome, smoking and respiratory disorders, this book is essential reading.